Association of serum neutrophil gelatinase associated lipocalin (NGAL) levels with preeclampsia - Dhivya, M.; Mathew, Chippy Tess; Jeyachandran, G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is a systemic disorder that affects multiple organs and is characterized by the new onset of hypertension and proteinuria or end-organ dysfunction or both in the second half of pregnancy. NGAL is a 25-KDa protein of the lipocalin family and is considered to be a novel biomarker for ischemic injury. The objective of this study is to compare the levels of serum NGAL in preeclamptic patients and gestational age matched normotensive controls. Methods: The study design is case control study in which pregnant women with preeclampsia (n=40) are selected as cases. Cases were selected from pregnant women attending OG-OPD and IP satisfying the inclusion criteria and not coming under exclusion criteria. 0.5ml of blood was collected in vacutainers and was centrifuged at 3500rpm for 10 minutes. The serum thus separated was aliquoted into smaller plain containers and stored at -20 degree Celsius for analysis. The urine sample was also collected. Controls were also selected from the OP patients. Results: In present study, the serum NGAL ranged from 40-900ng/ml in cases and from 110-795ng/ml in controls. There is no difference in NGAL between cases and control. The correlation coefficients between the NGAL levels and other parameters like maternal age, gestational age, systolic Blood pressure, diastolic Blood pressure, uric acid levels, urine PCR are also not statistically significant. Conclusions: Serum NGAL levels are not significantly elevated in patients with preeclampsia when compared with the normotensive controls and also there is no significant correlation between serum NGAL levels and other assessed parameters.